Finding First-Year Success in Extension: Navigating Stakeholder Needs and Institutional Expectations - Donald A. Llewellyn (Journal of Human Sciences and Extension, 2013)
Functioning within a defined administrative framework and meeting the needs of the stakeholders are essential in an Extension appointment. The first day of employment starts the promotion and tenure clock. It is the responsibility of the new Extension professional to take immediate steps to move forward with development of programming and application of the skill set that they bring to the job. Finding success in the first year of an Extension appointment revolves around understanding the expectations of the institution and the needs of the stakeholders. Once the institutional expectations and programming needs are understood, formulating a strategy that includes plans of work and logic models, measurement of outcomes and impacts, team building, professional development, peer mentoring, grant writing, and scholarship will provide a foundation for first-year success in Extension. A willingness to follow a timely and systematic approach to meeting the expectations of the institution and stakeholders will provide for an efficient transition and relieve many of the stressors associated with a new appointment. This paper is based primarily on the author’s first year experience as an Extension faculty member and summarizes several best practices.